Comparision of caloric intravenous solutions for hypothermic preserving of Vietnamese stem cells from exfoliated deciduous teeth - Nguyen, Thi Thuy Ngan; Ha, Tran Bao Chau; Do, Vinh Truong; Le, Thi Khanh Huyen; Nguyen, Thi Hiep; Nguyen, Doan Son; Chu, Hoang Ha; Nguyen, Thi Sam (Vietnam Journal of Biotechnology, 2025)
Mesenchymal stem cells from human exfoliated deciduous teeth (SHED), providing significant potential as regenerative medicine due to their multipotency, immunomodulatory properties, and non-invasive collection process. Effective preservation strategies are essential to maintain their quality during storage and transportation for clinical applications. This study evaluated the effects of two caloric intravenous solutions, Dextrose 5% (D5) and Dextrose 5% in Lactated Ringer (D5LR), on the hypothermic storage of SHED derived from Vietnamese donors. SHED was cultured and characterized for immunophenotyping, as well as osteogenic and adipogenic differentiation potential, prior to preservation. The cells were stored at 4°C or 25°C in D5 or D5LR for durations of 2, 4, and 6 hours, and post-storage assessments included cell viability, adhesion, and proliferation capacity. Results showed that D5 preserved higher cell viability and adhesion rates, with storage at 25°C achieving a 75% initial survival rate within 4 hours before declining significantly at 6 hours. Storage at 4°C maintains better adhesion, while proliferative capacity remained unaffected under both conditions. In contrast, SHED stored in D5LR exhibited lower viability, with dramatic declines in adhesion and a complete loss of proliferative capacity under both storage temperatures. In conclusion, D5 proved effective for short-term hypothermic storage of SHED, preserving key cellular properties critical for regenerative applications. Conversely, the solution of D5LR significantly compromised cell functionality, underscoring its unsuitability for clinical use. Notably, this study also represents the first reported successful isolation of SHED from Vietnamese dental tissue, further enhancing its significance. Additionally, these findings support D5 as a practical solution for preserving SHED quality in regenerative medicine.